Severe dual fungal infection after bispecific antibody therapy: A case of invasive aspergillosis and mucormycosis in immunocompromised patient - Sarah Sakalihasan; Frédéric Lifrange; Mathieu Czajkowski; Veronique Goncette; Bernard Duysinx; Pierre Lovinfosse; Damla Can; Raphael Schils; Marie-Pierre Hayette; Adrien De Voeght (IDCases)
Bispecific antibody is a new treatment for hematological disease, especially for lymphoma, myeloma and acute lymphoblastic leukemia. This class of treatment presents the same kind of side effect as CAR-T cell which are immune-mediated. Nevertheless, infectious complication remains a major concerns with related mortality. Fungal infection are rarely reported in clinical trial but remains a major concern. We report a case of a co-infection of Aspergillus and Mucorales in a patient with diffuse large B-cell lymphoma (DLBCL) following treatment with the bispecific antibody epcoritamab. The patient developed severe cytokine release syndrome (CRS) and subsequent fungal infections, which were challenging to diagnose and treat due to the complexities of managing immunocompromised patients and co-infection. Advanced diagnostics, including PET-CT, and a combination of antifungal therapies were crucial in achieving remission. The case underscores the need for early diagnosis, multidisciplinary management, and innovative treatment strategies in similar high-risk patients.